Fixed wireless routes for Internet access. - Dutta-Roy, A. (IEEE spectrum)
The author discusses the use of fixed radio access in urban and rural locations for Internet access. The costs involved are discussed and compared to wired access costs. The frequency bands available are considered as are the propagation conditions and antenna aspects